Dilemmas of regional geography of Slovenia - Klemenčič, Marijan (Journal for Geography, 2008)
The article calls the attention to the fact that regional geography in Slovenia suffers from methodological and theoretical weakness. Critical view on achievements of regional geography is done together with some entries to more complete study of geography of Slovenia.